Предмет: Математика,
автор: XSasha317
Решите уравнения:
(х+2)/5=(3х−5)/4
(6х+7)/7 - 3 = (5х-3)/8
(3-х)/12 =(-х+6)/8
Ответы
Автор ответа:
1
Ответ:
1.) (x+2)/5=(3x-5)/4 |*20
4*(x+2)=5*(3x-5)
4x+8=15x-25
-11x=-33
x=3
2.) (6x+7)/7-3= (5x-3)/8 |*56
8*(6x+7)-168= 7*(5x-3)
48x+56-168= 35x-21
13x = 91
x = 7
3.) (3-x)/12 = (-x+6)/8 |*96
8*(3-x) = 12*(-x+6)
24-8x = -12x+72
4x = 48
x = 12
Похожие вопросы
Предмет: Русский язык,
автор: masha333333
Предмет: Алгебра,
автор: Darhan26
Предмет: Биология,
автор: Евгеша20001306
Предмет: История,
автор: киска2627